RUSSIA'S RELATIONS WITH THE EUROPEAN UNION AND CHINA: COMPARATIVE ANALYSIS OF MUTUAL PERCEPTION IN THE BORDER REGIONS - R. H. Simonyan; T. M. Kochegarova (Vestnik MGIMO-Universiteta)
Occurred nearly a quarter of a century ago, the collapse of the Soviet Union - an event that led to the formation of a new configuration of the world-system. In this global role, the national significance of this event for Russia that she has to find their place in the world that actualizes a scientific discussion on this topic. Without public clarification and comparison of the ideological differences and disagreements it is difficult to imagine the development of a democratic society. Moreover, it is impossible to do without a debate in the society, standing in the darkness. Russia again, as in the beginning 1990-h years is in a situation of historical bifurcation. Russia to go their own way or try to rebuild themselves in the experience of the successful modernization of the States of the European, Asian, South American or African. They have used the Western (European) experience, without losing their national identity. Inherent in our ethnic consciousness and the inclination to extremes, Russian intellectuals keen on totally unproductive debates, like the endless, which is between "Westerners" and "Slavophil's" (in the current language - "fundamentalists"). The notorious dichotomy becomes more and more absurd, Recalling the disputes of "points" and "dull bits" from the famous novel of Jonathan Swift. The country is a completely different choice - effectiveness and development or the inefficiency and backwardness, modernization or preservation of its political and economic model, developed by reformers in 1990-ies. Today, therefore, Russia should not deifying the West, than succeeded ones and not the deification of exclusivity, what more you want to succeed others, but strong awareness of the reality and the pursuit of maximum expediency, pragmatism in the development of the achievements of Western civilization. If Asian countries are to successfully adopt the European (Western) modernization experience, then Russia as a European country should be more favorable conditions. In line with what is happening in the country discussions on ways of socio-economic development of Russia and its role and place in the emerging new global configuration, interactions with neighbors, primarily with the European Union and China in the context of the prospects of replacing the existing economic model and the upcoming modernization. Need to know life plans, orientation and attitudes of the Russian youth, its ideas about the place of Russia in a changing world. how it links its future with the future of their country. In the upcoming modernization, the main burden of its implementation will fall on the current young generation of Russians. In this regard, the article analyzes survey results of University students in six Federal districts of Russia.